2009
DOI: 10.1016/j.cpc.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Program package for multicanonical simulations of U(1) lattice gauge theory

Abstract: 2016-03-19T19:12:06

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…With Bazavov [51] I have worked out a straightforward implementation of the Wang-Landau recursion for the case of a continuous energy variable. The basic steps are:…”
Section: Wang-landau Recursion and Parallelizationmentioning
confidence: 99%
“…With Bazavov [51] I have worked out a straightforward implementation of the Wang-Landau recursion for the case of a continuous energy variable. The basic steps are:…”
Section: Wang-landau Recursion and Parallelizationmentioning
confidence: 99%
“…In the case of D = 4 pure gauge SU(2), numerical results were checked with existing expansions [33], and it was found that the zeros stay away form the real axis as the 4-volume increases [18]. In the case of D = 4 pure gauge U(1) theory [34], we used the multi-canonical algorithm developed by Berg and Bazavov [35] to construct the density of states. For small volumes, we were able to locate the lowest zeros with a precision of order 10 −5 .…”
Section: Overviewmentioning
confidence: 99%
“…Additional checks were made by calculating the first three moments of n(S). For U (1) lattice gauge theory, multicanonical methods relying on the Biased Metropolis-Heatbath Algorithm [13] were used [14]. Using this U (1) density of states, we have calculated the plaquette distribution calculated at fixed β and checked that there is an approximately symmetric double peak near β = 0.979 for a 4 4 lattice.…”
Section: Fisher's Zeros From the Density Of Statesmentioning
confidence: 99%
“…2 in the context of LGT. New "topological" methods to locate Fisher's zeros in SU (2) and U (1) using numerical calculations of the density of states [12,14] are discussed in Sec. 3.…”
Section: Introductionmentioning
confidence: 99%